Cato Handbook For Policymakers, 7th Ed. - Boaz, David, 1953- (Cato Institute, 2009)
Offers policy recommendations from Cato Institute experts on every major policy issue. Providing both in-depth analysis and concrete recommendations, the Handbook is an invaluable resource for policymakers and anyone else interested in securing liberty through limited government.